Analysis of the Difficulty of Study Programs in Unimed in the Development of Quality Assurance Based on Accreditation - Abdurrahman Adisaputera; Isda Pramuniati; Syamsul Arif (Budapest International Research and Critics University, 2018)
Quality assurance efforts at higher education institutions today are largely determined by the value of accreditation obtained, both in the study program and higher education institutions. Of course various obstacles are faced for the implementation of accreditation. The purpose of this study is to describe and analyze the level of difficulty of the study program at Unimed in carrying out the development of an accreditation-based quality assurance program. The method used to achieve the objectives of the research is through a qualitative approach with descriptive methods. Based on the research that has been done, it can be concluded that the level of difficulty of the study program in Unimed in meeting the accreditation standards can be seen from the low acquisition scores in standards 4, 5 and 7 in the study program accreditation forms. The low value obtained from the standard-accreditation standards is influenced by the development of lecturers' resources in each study program to improve scientific publications in accredited national journals and / or reputable international journals, and the participation of the lecturers is a speaker at scientific forums such as national seminars and seminars international.